IMPROVING THE METHODOLOGY FOR ASSESSING THE LEVEL OF TAX COLLECTION (American Journal of Business Management, Economics and Banking, 2023)
In this article, the democratization and renewal of the society in Uzbekistan, the modernization and reform of the country’s economy fundamentally reorganize the activities of various sectors in a comprehensive way, the sectors, having acquired their own characteristics, form an integrated system in interdependence, therefore, the reforms implemented in the tax system of Uzbekistan are a socially oriented market. It is reflected that it should be aimed at decision-making of the economy and should provide economic stability, free conditions based on democratic principles for the activities of citizens and economic subjects.